The impact of wind–wave coupling with WBLM on coastal storm simulations. (December 2022) - Du, Jianting; Larsén, Xiaoli Guo; Chen, Sheng; Bolaños, Rodolfo; Badger, Merete; Yang, Yang
Abstract: A wave boundary layer model (WBLM) that is applied as a wind-input source function for the ocean surface wave model SWAN is further used in a wind–wave coupling system for the wind stress calculation in the atmospheric model WRF. The coupling system is used for the investigation of the modeling of coastal wind, wave, and wind stress during storms in the North Sea. In comparison with measurements and other studies in the literature, the modeled magnitude and spatial distribution of the drag coefficient and roughness length by WBLM outperforms the other four popular parameterization and physics-based methods. In addition, the WBLM coupling method produces a spatial variation of the surface wind speed in shallow waters affected by the bathymetry. Furthermore, the wind and waves simulated by the WBLM coupling method during 321 storms in the North Sea are evaluated with measurements. Results show that WBLM coupling method is reliable for the simulation of wind, wave, and wind stress in shallow waters during storms. Highlights: A Wave Boundary Layer Model is used for both wind stress and wave calculation in a wind–wave coupling system. Our model produces a spatial variation of roughness length and wind speed in shallow waters affected by the bathymetry. The new coupling method shows good quality in coastal wind, wave and wind stress simulations during storms.